The Effect of a Long-Term Artistic Gymnastic Training on Reaction Time of Male Gymnasts - Bahman Aalizadeh; Fatemeh-Sadat Hosseini (The Society of Aging and Physical Activity (SAPA), 2014)
Since there are variations in the reaction times of athletes in different sports, the aim of the present study was to evaluate the effectiveness of a specific training program on a simple reaction time of male gymnasts. In this longitudinal study, fourteen adolescent gymnasts (mean age 12.6 ± 2.1 years) were randomly selected to work out for 15 months in the artistic group. Simple reaction time was assessed by visual and auditory tests using computer software. The training resulted in a significant (P < 0.001) reduction in visual (0.33 ± 0.047 s vs. 0.30 ± 0.048 s) and auditory reaction time (0.31 ± 0.056 s vs. 0.27 ± 0.038 s). This study suggested an improvement in both reaction time tests over a long time of specialized training program. Artistic gymnasts had overall developed results of the tests that might be derived from exercise induced arousal, concentration and movement complexity in this sport.